A high energy density aqueous hybrid supercapacitor with widened potential window through multi approaches. (May 2019) - Zhang, Si-Wen; Yin, Bo-Si; Liu, Xi-Xia; Gu, Da-Ming; Gong, Hao; Wang, Zhen-Bo
Abstract: It is well known that high performance and long cycle stability are the most significant advantages of aqueous hybrid supercapacitors (AHSCs). However, low energy density has always restricted the development of AHSCs. Low energy density mainly comes from low voltage window and specific capacitance. If the above short slabs were solved, supercapacitors would be industrialized and widely used. Herein, A novel AHSC based on the optimized CoMoO4 /MnO2 nanowires/Ni foam (KF-CMNWs) electrode and modified alkali-treated carbon nanotubes film (M-CNTF) with K3 Fe(CN)6 in neutral aqueous Na2 SO4 electrolyte is reported. The positive electrode material effectively improved its electrochemical performance through a synergistic effect. In addition, some redox mediators are added to a common electrolyte so that the electrolyte can also provide extra capacity. In order to enlarge the overall voltage window, sodium ions are absorbed on the alkali-treated carbon nanotubes film by a method of electroreduction, and the activity of HER is effectively reduced. A very high voltage of 1.4 V for the negative electrode in aqueous Na2 SO4 electrolyte is reached. The AHSC has also a prominent long cycle life (>10, 000 cycles; 96.8% capacitance retention) and presents a high energy density of 62.9 W h kg −1 at a power density of 984 W kg −1 . More importantly, the full cell has a competitive voltage window (2.4 V). These excellent characteristics are expected to be applied in new energy storage devices. Graphical abstract: The AHSC has a prominent long cycle life (>10, 000 cycles; 96.8% capacitance retention) and presents a very high energy density of 62.9 W h kg −1 at a power density of 984 W kg −1 . More importantly, the full cell has a competitive voltage window (2.4 V), higher than other AHSCs. These excellent characteristics are expected to be applied in new energy storage devices.fx1 Highlights: The self-assembledKF-CMNWs/Ni//M-CNTF aqueous hybrid supercapacitor (AHSC) presents a 2.4 V voltage window. The device presents a high energy density of 62.9 W h kg −1 at a power density of 984 W kg −1 . A modified alkali-treated carbon nanotubes film (M-CNTF) is prepared.